Case report: Ectopic thyroid tissue found in a liver with hepatocellular carcinoma - Wang, Zhanbo; Yuan, Jing; Li, Jie (Frontiers in Surgery, 2022)
Background Concomitant intrahepatic ectopic thyroid is rare in patients with hepatocellular carcinoma. Thyroid follicular structures outside the hepatocellular carcinoma lesions are regarded as satellite nodules or intrahepatic metastases of hepatocellular carcinoma, which often leads to misdiagnosis and overtreatment of hepatocellular carcinoma patients. Case presentation We report the case of an 83-year-old man with moderately differentiated hepatocellular carcinoma (2.5 cm) whose liver contained ectopic thyroid tissue. An encapsulated, multinodular grayish-yellow mass and multiple satellite nodules were detected and removed by right hepatic lobectomy. Microscopically, the main tumor displayed a predominant trabecular, cord-like structure. Liver tissue 0.5 cm from the tumor had a benign-appearing follicular thyroid structure. The follicles contained colloid tissue and were lined with low cuboidal cells with scant cytoplasm; lymphatic tissue was also present in the area. The hepatocellular carcinoma cells were positive for hepatocyte antigen and glypican-3 and negative for cytokeratin 19. The follicular thyroid cells expressed thyroglobulin, PAX8, and thyroid transcription factor-1. A metastatic thyroid neoplasm was excluded clinically and by ultrasound and computed tomography. One month after surgery, all of the patient's serological markers were normal; no tumor recurrence or metastasis has been detected for 7 postoperative months. Conclusions The finding of ectopic thyroid tissue in the liver of a patient with hepatocellular carcinoma is very rare. The possibility of hepatocellular carcinoma forming satellite nodules and intrahepatic metastasis should be ruled out first and immunohistochemistry may be definitive in making the diagnosis. Further examination is needed to exclude thyroid cancer liver metastases.